Pengaruh Beban Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Badan Narkotika Nasional Provinsi DKI Jakarta: The Effect of Workload and Work Motivation on the Performance of Employees of the National Narcotics Agency of DKI Jakarta Province - Maulidya Aprilia; Lela Elvira; Maria Lapriska Dian Ela Revita (PT Cakrawarti Empat Proksi, 2026)
In the current development of the work world, human resources have an important role in achieving organizational goals. The National Narcotics Agency of DKI Jakarta Province is one of the government agencies tasked with the prevention, eradication, abuse, and illicit trafficking of narcotics. This study aims to determine the effect of workload, work motivation on the performance of employees of the National Narcotics Agency of DKI Jakarta Province. The method used is quantitative research with data collection through distributing questionnaires, so that 76 employees were obtained. Data were analyzed using SPSS version 21. through classical, partial, simultaneous assumption tests, coefficient of determination, and regression. The results of the study indicate that Workload has a positive and significant effect on Employee Performance with t count 4.047> t table 1.663 and sig 0.000 <0.05. Work Motivation has a positive and significant effect on Employee Performance with t count 6.541> t table 1.663 and sig 0.000 <0.05. Workload and Work Motivation simultaneously have a positive and significant effect on Employee Performance with F count 70.978 > F table 3.12 and sig 0.000 < 0.05.